SARAWAK PUA KUMBU : AESTHETICS LIES IN THE EYE OF THE BEHOLDER - Saiful Bahari, Hj Mohd Yusoff; Noorhayati, Saad; Wan Juliana, Emeih Wahed (Universiti Teknologi MARA, 2019)
The beauty of Pua Kumbu is not merely a cultural expression but also represents the wealth of information to pass from one generation to another. The art of creating Pua Kumbu design motifs is based on the body of knowledge gathered through collective memory, and the conservation of Pua Kumbu's knowledge and history. The aesthetic perception stimuli from the audiences are complicated cognitive processes. Hence, this study aims to measure the aesthetic perception of 400 participants about design motifs applied on the cloth according to their gender and background using ARS-Revised questionnaire. The findings revealed that female participants exhibited a greater knowledge of Pua Kumbu compared to their male counterparts. Participants from Sarawak perceived higher in cognitive stimulation, knowledge, and self-reference which indicated that they were more likely to be knowledgeable about Pua Kumbu. Participants from Sabah demonstrated the lowest in both cognitive stimulation and expertise despite Sabah being situated in the same region as Sarawak; Borneo. Gender and background of the participants are concluded to exert significant influence on the knowledge in Pua Kumbu design motifs. Knowledge of Pua Kumbu is crucial for the appreciation of aesthetic in preserving the culture and heritage of Sarawak, Malaysia at its best.